The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.2134/jeq2009.0105
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Pharmaceuticals in Columns of a Wastewater‐Irrigated Mexican Clay Soil

Abstract: The irrigation or agricultural land with wastewater is increasingly practiced in many parts of the world as a consequence of growing populations and urbanization. The risks emerging from pharmaceuticals that are contained in wastewater for soils and groundwater have hardly been investigated. We studied leaching and effects of naproxen, ibuprofen, bezafibrate, diclofenac, gemfibrocil, clarithromycin, trimethoprim, clindamycin, erythromycin, and metoprolol in a soil column experiment simulating an irrigation eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…The concentrations of these acidic pharmaceuticals in soils did not increase with increasing time of wastewater irrigation (Table S6). This lack of accumulation confirms the results of Siemens et al [14], [60] and Durán-Álvarez et al [61] regarding the poor retardation of these compounds in soil. Due to the alkaline pH values of the wastewater and the receiving soils that exceed the acid dissociation constants of naproxen, diclofenac, and bezafibrate, these compounds occur as negatively charged species.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The concentrations of these acidic pharmaceuticals in soils did not increase with increasing time of wastewater irrigation (Table S6). This lack of accumulation confirms the results of Siemens et al [14], [60] and Durán-Álvarez et al [61] regarding the poor retardation of these compounds in soil. Due to the alkaline pH values of the wastewater and the receiving soils that exceed the acid dissociation constants of naproxen, diclofenac, and bezafibrate, these compounds occur as negatively charged species.…”
Section: Resultssupporting
confidence: 88%
“…This negative charge counteracts sorption to negatively charged clays and moieties of soil organic matter [14], also expressed by small K OC values at near neutral pH (Table 2). In the column experiments of Siemens et al [60] with soil from the Mezquital Valley degradation of naproxen could not be detected while bezafibrate transport could be described with a first order degradation rate constant of 0.033±0.03/h.…”
Section: Resultsmentioning
confidence: 89%
“…The antibiotics, such as tetracyclines and quinolones (QNs), exhibit high adsorption properties to accumulate in soil on the surface of either mineral or organic soil constituents (Tolls 2001). On the other hand, they have additional risk for contaminating groundwater resources due to the migration water containing antibiotics (Heberer et al 2008;Siemens et al 2010;Ternes et al 2007). Moreover, antibiotic residues in soil can result in the emergence of antibiotic resistance genes, which will be a new threat to public health (Knapp et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, to some extent, such management may result in negative consequences such as organic or inorganic contamination of soil. Several studies have been conducted to explore the occurrence and fate of antibiotics in the agricultural soil after long-term wastewater irrigation or fertilization using animal manure (Dalkmann et al 2012;Hamscher et al 2002;Hu et al 2010;Karcı and Balcıoğlu 2009;Kinney et al 2006;Ostermann et al 2014;Shi et al 2012;Siemens et al 2010;Tamtam et al 2011;Ternes et al 2007). However, the studies on the occurrence and distribution of antibiotics in urban soil are still less reported.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the passage of treated wastewater through the soil, batch and soil column experiments are commonly used to estimate sorption parameters, and microcosm experiments used to investigate plant uptake [20,21]. While standard laboratory experiments with defined boundary conditions yield comparable results, their extrapolation to real field conditions characterized by heterogeneous soil layers and accompanying physico-chemical properties, specific hydrological and climatic conditions, and diverse communities of microorganisms and plants is challenging and may considerably deviate from the findings of actual field-scale investigations [22].…”
Section: Introductionmentioning
confidence: 99%